Experion - a framework for expertise retrieval: fact-based context injection in expert finding systems for multiple contextualized result interpretations - Gonçalves, Rodrigo (2023)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Ciência da Computação, Florianópolis, 2023.